IMPLEMENTASI CSR PT PLN (PERSERO) UIP JBTB II PADA PEMBERDAYAAN KOMUNITAS DISABILITAS BATIK WISTARA - Arifin, Zainul; Huda, Anam Miftahul (Universitas Negeri Surabaya, 2024)
Implementing corporate social responsibility is certainly one form of building a public image for a company, because in order to increase profits or win a positive image for society, of course there must be a real effort and impact for the company on society in particular. This is of course what PLN UIP JBTB always strives for in carrying out its obligations as one of the front guards in the construction and transmission unit of PT PLN (Persero). Meanwhile, through this thesis research, the researcher tries to analyze the success of the implementation of the social responsibility program carried out by PLN UIP JBTB. One of the implementation programs is in collaboration with Batik Wistara, the program is an effort to empower disabled groups to work and develop their potential through Batik production in the city of Surabaya. Researchers conducted this research with the hope that in the future a good social responsibility program can emerge by making this research a benchmark for programs from other companies.